Neurological and Mental Development of Low-Birth~ Weight Infants (A Preliminary Report) - S.K. Hendarto; Sofyan Ismael; Rulina Suradi; H.E. Monintja (Paediatrica Indonesiana, 1980)
Fifty- two low birth weight infants were examined with a minimal age of 2 years and nine months old. Neurologic abnormalities were very high (38.8%). Convulsions predominate the other abnormalities (21.2%). followed by other abnormalities respectively cerebral palsy, multiple handicapped, mental retardation, behaviour disorders, speech problems, hearing defect and minimal abnormalities. Neuroiogic impairments were found more in the group of children with weight between 2000 - 2500 grams; and on the appropriate for their gestational age compared to the small for gestational age children. Intelligence tests on 27 children revealed approximately 50% had an I.Q. below the normal range. A remarkably high incidence of abnormal EEG recordings (50%) were detected, even on neurologically normal and abnormal infants children did not reveal a distinct correlation with the outcome of these infants.